PERENCANAAN DAN PEMANFAATAN POWERPOINT SEBAGAI MEDIA DALAM PEMBELAJARAN PAI DI SMP IT AL-HIDAYAH TENGGARONG - Akhmad Riadi; Maryam; Falisha Ramadhani; Julia Muryani; Chusnul Chotimah; Annisa Fathimadhani; Nayla Alwiyatuzzahra (Institut Ummul Quro Al-Islami Bogor, 2026)
This study aims to analyze the planning, implementation, and effectiveness of PowerPoint media in Islamic Religious Education (PAI) learning at SMP IT Al-Hidayah Tenggarong. The research employed a descriptive qualitative approach using field research methods through observation, interviews, and documentation. The findings indicate that the use of PowerPoint can improve students’ attention, motivation, and understanding of PAI materials when it is designed according to instructional objectives and supported by proper preparation. PowerPoint helps teachers present learning materials in a more interesting, systematic, and interactive manner through the combination of text, images, videos, and animations. However, its implementation still faces several obstacles, such as limited facilities, unequal technological competence among teachers, and limited time for preparing learning media. Therefore, school support through the provision of facilities and continuous training is needed to optimize the use of PowerPoint in PAI learning